Prevalence and clinical characteristics of Danon disease among patients with left ventricular hypertrophy and concomitant electrocardiographic preexcitation. Issue 5 (30th March 2019) - Liu, Yang; Chen, Xin; Wang, Feng; Liang, Yingcong; Deng, Hai; Liao, Hongtao; Zhang, Qianhuan; Zhang, Bin; Zhan, Xianzhang; Fang, Xianhong; Shehata, Michael; Wang, Xunzhang; et al.
Abstract: Background: Cardiac involvement in Danon disease typically manifests as left ventricular hypertrophy (LVH) and ventricular preexcitation. This study aimed to identify patients with Danon disease among patients with LVH and concurrent electrocardiographic preexcitation. Methods: Electrocardiographic preexcitation was identified in 10 of 197 patients with unexplained LVH in whom genetic testing was performed using next‐generation sequencing. Results: Three (3/10, 30%) patients with Danon disease were found in association with different mutations in the gene of lysosome‐associated membrane protein 2 ( LAMP2 ). Compared to seven patients without Danon disease, these three patients presented with distinctive clinical phenotypes, including onset at an earlier age (20 ± 2 years vs. 53 ± 9 years, p < 0.001), more neurological involvements (100% vs. 0, p = 0.008), higher electrocardiographic voltages (10 ± 1 mV vs. 5 ± 1 mV, p < 0.001), wider QRS complexes (163 ± 5 ms vs. 115 ± 20 ms, p = 0.006), less common asymmetric hypertrophy (0% vs. 86%, p = 0.033), and more frequent elevation of three serum enzymes (creatine kinase, aspartate aminotransferase, and lactate dehydrogenase). Intracellular vacuoles accumulation with deficiencies of LAMP2 protein was found in both cardiac and skeletal myocytes of patients with Danon disease. Conclusion: In patients with coexistent LVH and ventricular preexcitation, Danon disease is common with distinctive clinical presentations. Comprehensive assessment of these resemble patients can provide valuable findings for early identification and clinical decision making of patients with Danon disease. Abstract : In patients with coexistent LVH and ventricular pre‐excitation, Danon disease is common with distinctive clinical presentations. Comprehensive assessment of these resemble patients can provide valuable findings for early identification and clinical decision making of patients with Danon disease.